Vietnam : 2006 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Vietnam. (IMF Staff Country Reports; Country Report, 2006)
Overall, macroeconomic performance has remained strong since the conclusion of the last Article IV Consultation. The authorities have introduced market-opening legislation in line with WTO requirements, but state-owned commercial banks (SOCBs) and state-owned enterprise (SOE) reforms remained uneven. The short-term outlook is broadly positive, but medium-term prospects are subject to risks. IMF staff supports the State Bank of Vietnam's (SBV's) plan to establish a more flexible exchange rate regime. The balance of payments has remained in surplus.